Communication and education in network society - Quiroz, Teresa (2007)
A glance of the challenges of the society and the new culture of capitalism is offered for education, characteristics of Nerwork Society as well as the possibilities and risks it poses. Ways which allow us to rethink and to recreate the education and the communication from the person and his possibilities of interactive action are propose.